The behavioural intentions for integrating artificial intelligence in science teaching among pre-service science teachers in South Africa and Thailand - Lindelani Mnguni; Prasart Nuangchalerm; R. Ahmad Zaky El Islami; Doras Sibanda; Indah Juwita Sari; Moleboheng Ramulumo (Computers and Education: Artificial Intelligence)
Developing countries in the Global South exhibit diverse trends in the integration of digital technologies, such as Artificial Intelligence in teaching. Complex context-specific factors, including teacher preparedness, influence these trends. Using the Theory of Planned behavior as a theoretical framework, this study explores the behavioral intentions of pre-service science teachers in South Africa and Thailand towards integrating AI into their teaching to inform teacher training, support, and resource allocation policies. The main research question is: ''What are the behavioral intentions of pre-service science teachers in South Africa and Thailand towards integrating AI into their teaching practices?'' The study followed a non-experimental comparative descriptive survey involving 97 South African and 95 Thai final-year BEd students. Data were collected using a structured online questionnaire and analyzed using several statistical tools to compare the TPB constructs between the two samples. South African and Thai pre-service teachers exhibited favorable attitudes and behavioral intentions toward AI integration in teaching. However, Thai students showed significantly higher control and normative beliefs, indicating greater confidence and perceived social support for AI integration than South African students. The findings suggest that targeted teacher training programs and supportive educational policies are essential for enhancing AI readiness, particularly in resource-constrained settings.